Oral Health in Systemic Disease: Integrated Clinical Considerations and Interprofessional Care Pathways for Dental, Medical, and Allied Health Professionals - Al-Hejji, Ahmed Jaber Mohammed; Zahraa Hussain Saleh Al Nasser,; Wadiah Yousef Alhamdan,; Zainab Ali Hassan Aloufi,; Zainab Mustafa Mohsan Al Hassan,; Saad Abdulrahman Alsaadi,; Abdulaziz Ali Ibrahim Bussanah,; Zainab Nuri Ali Alghirash,; Mohammed Matar Al-Anzi, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Oral health is deeply interconnected with systemic health, yet dental care is often perceived as isolated from medical practice. Invasive dental procedures can trigger systemic responses, especially in patients with chronic conditions, making integrated care essential. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This paper aims to outline clinical considerations and interprofessional strategies for delivering safe dental care to patients with systemic diseases, emphasizing risk assessment, procedural modifications, and collaborative care pathways. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of current literature and clinical guidelines was conducted, focusing on oral–systemic interactions, risk stratification frameworks, and evidence-based recommendations for managing medically complex patients during invasive dental procedures. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Findings reveal that systemic conditions such as hypertension, cardiovascular disease, immunosuppression, coagulopathy, and cancer significantly influence dental treatment planning. Risk assessment tools like ASA classification, Charlson Comorbidity Index, and dental-specific models provide structured decision support. Key modifications include stress-reduction protocols, epinephrine limitation in hypertensive patients, antibiotic prophylaxis for high-risk cardiac conditions, and tailored strategies for immunocompromised individuals. Integration of interoperable health records, interprofessional education, and standardized protocols emerged as critical solutions to overcome structural and behavioral barriers. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Safe dental care for medically complex patients requires a shift from isolated practice to integrated, patient-centered models. Interprofessional collaboration, comprehensive risk assessment, and proactive oral health optimization before systemic therapies are essential to reduce complications and improve outcomes.